Arterial hypertension and atrial fibrillation: standard and advanced echocardiography from diagnosis to prognostication. Issue 2 (February 2018) - Cameli, Matteo; Mandoli, Giulia E.; Ambrosio, Giuseppe; Cerbai, Elisabetta; Coiro, Stefano; Emdin, Michele; Marcucci, Rossella; Morrone, Doralisa; Palazzuoli, Alberto; Savino, Ketty; Padeletti, Luigi; Mondillo, Sergio; et al.
Abstract : N/A: Structural changes in left and right cardiac chambers that occur in arterial hypertension (AH) may lead to an increased risk of atrial fibrillation. Considering that AH is currently the most common cardiovascular disease in the general population, it represents a major risk factor for atrial fibrillation development. This review explores the complex relationship between atrial fibrillation and AH, starting from its pathophysiological basis. It focuses on the role of echocardiography in the management of hypertensive and atrial fibrillation patients, with emphasis on what should be evaluated about left ventricular remodeling, diastolic and systolic function, left atrial (LA) size and function and right ventricular deformation in patients with AH.